The contribution of elasticresistance during the eccentric phase of a countermovement jump enhances performance. - Aboodarda, S.J.; Yosuf, A.; Abu Osman, Noor Azuan; Thompson, M.W.; Mokhtar, A.H. (Human Kinetics, 2012)
The purpose of the present study was to identify the effect of additional elastic force on the kinetic and kinematic characteristics as well as the magnitude of leg stiffness during the performance of accentuated CMJs. Fifteen trained male subjects performed three types of CMJ including FCMJ (i.e. body weight), ACMJ-20 and ACMJ-30 (i.e. accentuated eccentric CMJ with downward tensile force equivalent to 20 and 30 body mass, respectively). A force platform synchronized with six high-speed infra-red cameras was used to measure vertical ground reaction force and displacement, respectively. The results demonstrated that using downward tensile force during the lowering phase of a CMJ and releasing the bands at the start of the concentric phase increased maximal concentric VGRF (6.34), power output (23.21), net impulse (16.65), and jump height (9.52) in ACMJ-30 compared with FCMJ (all p < .05). However, no significant difference was observed in the magnitude of leg stiffness between the three modes of jump. The results indicate that using downward recoil force of the elastic material during the eccentric phase of a CMJ could be an effective method to enhance jump performance by applying a greater eccentric loading on the parallel and series elastic components coupled with the release of stored elastic energy. The importance of this finding is related to the proposition that power output, net impulse, takeoff velocity and jump height are the key parameters for successful athletic performance and any training method that improves impulse and power production may improve sports performance particularly in jumping aspects of sport.